Formalizing employment in Africa's small firms: Experimental evidence from Côte D'Ivoire - Katharina Fietz; Tabea Lakemann; Bernd Beber; Jan Priebe; Jann Lay (RWI - Leibniz-Institut für Wirtschaftsforschung, 2025)
Informal, low-quality employment in micro, small, and medium enterprises (MSMEs) remains a significant challenge in low- and middle-income countries. We present evidence from an impact evaluation of a light-touch business consulting program with a focus on employment formalization in Côte d'Ivoire. Using a randomized controlled trial with 448 MSMEs and a unique employer-employee dataset, we find that the intervention led to employment formalization, driven by greater reported minimum wage compliance and an increase in written contract provision. We show suggestive evidence that these improvements were driven by selective formalization and increased awareness of regulation. The intervention's financial implications were moderate, with findings indicating that firms partially formalized previously informal payment streams, without a significant increase in total labor costs. – – Informelle, niedrigqualitative Beschäftigung in Mikro-, kleinen und mittleren Unternehmen (MSMEs) bleibt eine bedeutende Herausforderung in Ländern mit niedrigem und mittlerem Einkommen. Wir zeigen Evidenz aus einer Wirkungsevaluierung eines niedrigschwelligen Unternehmensberatungsprogramms mit Fokus auf die Formalisierung von Beschäftigung in Côte d'Ivoire. Mithilfe einer randomisierten kontrollierten Studie mit 448 MSMEs und einem innovativen Arbeitgeber-Arbeitnehmer-Datensatz stellen wir fest, dass die Intervention zur Formalisierung von Beschäftigung führte, angetrieben durch eine stärkere Einhaltung des Mindestlohns und eine Zunahme der Bereitstellung schriftlicher Verträge. Hinweise deuten darauf hin, dass diese Verbesserungen durch selektive Formalisierung und ein erhöhtes Bewusstsein für Regulierung bedingt waren. Die finanziellen Auswirkungen der Intervention waren moderat. Die Ergebnisse legen nahe, dass Unternehmen zuvor informelle Zahlungsströme teilweise formalisierten, ohne dass es zu einem signifikanten Anstieg der Gesamtarbeitskosten kam.
Keywords: O12; O17; J46; J81; 330; Employment formalization; business consulting; micro; small and medium enterprises(MSMEs); randomized controlled trial (RCT); Côte d'Ivoire